(Un)making Modernity and Modernisation: A conceptual Inquiry - De Silva, Premakumara (My University, 2009)
The world about us has changed and is continually changing at an everaccellerating [sic] pace. So have we. With the increase in media coverage and information technology, we see more of the world, comprehend its working a little more clearly, and as a result our perception of ourselves and the society surrounding us has been modified. Consequently, we begin to make demands upon the art and culture that is meant to reflect the constantly shifting landscape we find ourselves in. We demand new themes, new insights, new dramatic situations. We demand new heroes (Alan Moore, 'An Introduction' to Frank Miller's The Dark Knight Returns).